The Role of Physical Education and Sports in Shaping the Nation's Character - Salahudin, Salahudin; Ewan Irawan; Furkan, Furkan (Champions: Education Journal of Sport, Health, and Recreation, 2024)
Physical education and sports play a crucial role in shaping the nation's character. Through a holistic approach, this education not only enhances physical fitness but also instills fundamental moral, social, and leadership values for both individual and societal development. This study delves into the significance of physical education and sports as a cornerstone in nation-building. We highlight their vital contributions in fostering discipline, cooperation, sportsmanship, and other positive values essential for cultivating strong and responsible personalities. The analysis explores various methods and approaches for effective implementation of physical education and sports, emphasizing the importance of integrating academic and non-academic curricula to create sustainable and holistic learning environments. By strengthening the role of physical education and sports within the education system, we can nurture a healthier, more competitive, and morally responsible generation for building the nation's future.